Vaccine Effectiveness Against Prevalent Anal and Oral Human Papillomavirus Infection Among Men Who Have Sex With Men—United States, 2016–2018. (6th June 2020) - Meites, Elissa; Winer, Rachel L; Newcomb, Michael E; Gorbach, Pamina M; Querec, Troy D; Rudd, Jessica; Collins, Tom; Lin, John; Moore, Janell; Remble, Thomas; Swanson, Fred; Franz, Justin; et al.
Abstract: Background: In the United States, human papillomavirus (HPV) vaccination has been recommended for young adult men who have sex with men (MSM) since 2011. Methods: The Vaccine Impact in Men study surveyed MSM and transgender women aged 18–26 years in 3 US cities during 2016–2018. Self-collected anal swab and oral rinse specimens were assessed for 37 types of HPV. We compared HPV prevalence among vaccinated and unvaccinated participants and determined adjusted prevalence ratios (aPR) and 95% confidence intervals (CI). Results: Among 1767 participants, 704 (39.8%) self-reported receiving HPV vaccine. Median age at vaccination (18.7 years) was older than age at first sex (15.7 years). Quadrivalent vaccine-type HPV was detected in anal or oral specimens from 475 (26.9%) participants. Vaccine-type HPV prevalence was lower among vaccinated (22.9%) compared with unvaccinated (31.6%) participants; aPR for those who initiated vaccination at age ≤18 years was 0.41 (CI, 0.24–0.57) and at age >18 years was 0.82 (CI, 0.67–0.98). Vaccine effectiveness of at least 1 HPV vaccine dose at age ≤18 years or >18 years was 59% and 18%, respectively. Conclusions: Findings suggest real-world effectiveness of HPV vaccination among young adult MSM. This effect was stronger with younger age at vaccination. Abstract : Among 1767 men who have sex with men and transgender women aged 18–26 years in US cities during 2016–2018, vaccine-type HPV prevalence was lower among vaccinated (22.9%) compared with unvaccinated (31.6%) participants, suggesting real-world effectiveness of HPV vaccination.